Measurement of the inclusive tt production cross section in the lepton + jets channel in pp collisions at √s=7 TeV with the ATLAS detector using support vector machines - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; et al. (Physical review, 2023)
A measurement of the top quark pair-production cross section in the lepton+jets decay channel is presented. It is based on 4.6 fb−1 of √s=7 TeV pp collision data collected during 2011 by the ATLAS experiment at the CERN Large Hadron Collider. A three-class, multidimensional event classifier based on support vector machines is used to differentiate t¯t events from backgrounds. The t¯t production cross section is found to be σt¯t=168.5±0.7(stat) +6.2−5.9(syst) +3.4−3.2(lumi) pb. The result is consistent with the Standard Model prediction based on QCD calculations at next-to-next-to-leading order.